Influence of La incorporation on the catalytic activity of Ru/ETS-10 catalysts for hydrogen production - Faroldi, Betina María Cecilia (2015)
The incorporation of lanthanum on ETS-10 titanosilicate and its influence on the catalytic activity of Ru catalysts for the dry reforming of methane reaction were studied. The catalysts were prepared through ion exchange of ETS-10 using different lanthanum solution concentrations (0.1, 0.2 and 0.4 % wt of La2O3). The Ru loading was 0.6 wt.% for all catalysts. The methane reaction rates for Ru/LaETS-10 catalysts showed an increase in comparison with Ru/ETS-10. This could be related to the lanthanum participation in the reaction mechanism. Moreover, all the formulations were stable after 70 h on stream. In order to study the effect of lanthanum exchange in the structure of ETS-10 supports, the solids were characterized by BET, XRD, TEM, FTIR XPS, and Laser Raman spectroscopy. The relative crystallinities were lower than 80%, indicating that the La exchange could have an important effect on the crystalline structure of ETS-10, in agreement with Raman and FTIR results. The surface Ru/Ti ratio determined by XPS was higher in the case of Ru/LaETS-10 synthesized with the highest La concentration in the exchange solution. The Na/Ti ratio, measured by XPS and EDX, was lower for the Ru/LaETS-10 catalysts compared with ETS-10 suggesting that La was exchanged in the structure.